Prototype Gelang Tangan Pendeteksi Jarak Physical Distancing Man To Man - Robi Dwi Putra; Rahmi Eka Putri (Universitas Andalas, 2021)
This research is motivated by the phenomenon of the Covid-19 pandemic in several countries, one of which is in Indonesia. To avoid Covid-19 infection, the government has implemented several policies such as physical contact restrictions (physical distancing). When implementing physical distancing, a person is not allowed to shake hands and maintain a distance when interacting with other people, especially with people who are sick or at high risk of suffering from COVID -19. However, on the other hand, the physical distancing policy that has been implemented has not been maximized. This happens due to several factors. Among them is the existence of a misunderstanding in society that causes negligent nature in implementing physical distancing efforts. This journal focuses on the use of technology to calculate physical distance distances automatically using the calculation of the received signal strength indicator (RSSI) by utilizing Bluetooth low energy (BLE) as the communication medium. RSSI is a measurement of the power received by a wireless device. The basic principle of this system is the existence of connectivity between wristbands using Bluetooth communication media so that the system can calculate physical distance distances automatically using the RSSI value.